Lipid levels and the risk of hemorrhagic stroke among women - Rist, Pamela M; Buring, Julie E; Ridker, Paul M; Kase, Carlos S; Kurth, Tobias; Rexrode, Kathryn M (Neurology, 2019)
To examine the association between lipid levels and hemorrhagic stroke risk among women. We performed a prospective cohort study among 27,937 women enrolled in the Women's Health Study with measured total cholesterol, low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C), as well as triglycerides. Strokes were confirmed by medical record review. We used Cox proportional hazards models to analyze associations between lipid categories and hemorrhagic stroke risk. During a mean of 19.3 years of follow-up, 137 hemorrhagic strokes occurred. Compared to those with LDL-C levels 100-129.9 mg/dL, after multivariable adjustment, those with LDL-C levels <70 mg/dL had 2.17 times the risk (95% confidence interval [CI] 1.05, 4.48) of experiencing a hemorrhagic stroke. No significant increase in risk was seen for those with LDL-C levels 130-159.9 mg/dL (relative risk [RR] 1.14; 95% CI 0.72, 1.80) or 70-99.9 mg/dL (RR 1.25; 95% CI 0.76, 2.04). There was a suggestion, although not significant, of increased risk for those with LDL-C levels ≥160 mg/dL (RR 1.53; 95% CI 0.92, 2.52). Women in the lowest quartile of triglycerides had a significantly increased risk of hemorrhagic stroke compared to women in the top quartile after multivariable adjustment (RR 2.00; 95% CI 1.18, 3.39). We observed no significant associations between total cholesterol or HDL-C levels and hemorrhagic stroke risk. LDL-C levels <70 mg/dL and low triglyceride levels were associated with increased risk of hemorrhagic stroke among women.